CENTRAL BANK DIGITAL CURRENCIES (CBDCs) - Tursunova Ibodat Khujayor qizi (Journal Park Publishing, 2024)
This article covers the digital currency produced by the Central Bank - CBDC. That is, the main difference of the digital currency of the central bank from other digital currencies, its types and practical use have been theoretically studied. The practical situation and statistical data related to the implementation and development of this digital currency, as well as the countries that study and want to introduce this currency, have been researched. Also, along with the positive results of the CBDC, the risks affecting the country's economy as a result of its introduction were studied, systematized, and relevant conclusions and proposals were given.
Keywords: CBDC, digital currency, cryptocurrency, transactions, payment, money laundering, blockchain technology, retail, wholesale, interest rates, GDP, quantitative easing, financial stability, risk, operation risk.